Globalizing central Asian human resources and soft power of Japanese education - Kim, V.; Yem, N. (Journal of Oriental Studies, 2022)
This paper explores the impact of globalization on the career development of students from Central Asian countries who choose Japanese studies majors and the position of Japan in the process of their career decision-making. We examine the choices and possibilities of human resource development and higher education exchange in the two regions. In particular, (1) the image of Japan among students in Central Asian countries, (2) the reasons Central Asian students choose to acquire Japanese studies majors, and (3) the impact of studying in Japan on their careers. We will analyze these points from Japan's soft power perspective. This paper is based on the interview data collected by authors with fifteen students from Central Asian countries who majored in the Japanese language in their home universities in Kazakhstan, Uzbekistan, and Kyrgyzstan and have experience of studying for more than six months in Japan. We posit that Japan’s soft power, based on the popularization of cultural and language products, has strengthened in Central Asian countries over recent years. This led to the popularity of Japanese studies majors and receiving education in Japan among university students. As the relationship between Japan and Central Asian countries deepens, it is important to explore career opportunities and issues Japanese studies students face.